Impacto da raça, do escore corporal e da categoria animal na taxa de prenhez de fêmeas bovinas em manejo de IATF - Rosana Dias Campos (2020)
Reproductive biotechnologies such as artificial insemination in fixed (IAFT), can be used to maximize reproductive efficiency and facilitate management actions in cattle farming. Thus, this work was divided into two articles, article 1, with the objective of studying the impact of the reuse of the intravaginal progesterone implant (DIP), the body condition score and the racial composition on the pregnancy rate of Nellore and Angus (F1) and Nelore cows of different categories submitted to IATF protocols, from a database of 3,093 females submitted to the same hormonal induction protocol and from the mating season of a commercial farm in the north of Minas Gerais. The racial composition influenced the pregnancy rate of heifers, with rates of 55.11% for Nellore heifers and 64.36% for ½ Angus, showing that the ½ Angus breed has 1.55 times more chances of successful gestation compared to the breed Nellore. There is no effect of the progesterone implant until the third use on the pregnancy rate of the heifers evaluated. The increase of one unit in the body condition score on the scale of 1 to 5 implies 1.9109 or 91.09% times more success in pregnancy. The category of calving cows did not significantly affect the pregnancy rate in the evaluated herd, with pregnancy rates of 58.1%, 62.8%, 77.7% and 62.9% for primiparous, early primiparous, secondary and multiparous, respectively. The introduction of ½ Angus heifers to explore the effects of heterosis and complementarity between breeds is a viable alternative. Cows, when well managed in the postpartum period, obtain pregnancy rates higher than that observed in the national average. Article 2 aimed to evaluate the gestation rate of Nellore bovine females, submitted to exogenous application of the hormones gonadotropin-releasing (GnRH) and equine chorionic gonadotropin (eCG) applied on days 0 and 9 of the IATF protocol of calves and calves do not give birth. Cows were divided into 2 experimental groups according to each category evaluated. Group 1: non-calving cows: GnRH (received 0.25g of GnRH on day 0 of the IATF protocol) x Control and Group 2: calving cows: eCG (received 400UI of eCG on day 9 of the IATF protocol) x Control. Higher pregnancy rates were observed for the control group of calving and non-calving cows. With regard to the follicular diameter, females with follicles <13 mm had lower pregnancy rates when compared to animals with follicular diameter greater than or equal to 13 mm. Females in the control group with 61-68 days postpartum achieved a higher pregnancy rate than the eCG group, while cows with 99 days of calving reached a percentage of total pregnancy for both the control group and the eCG and control group. Additionally, multiparous cows from the GnRH and eCG and control groups obtained higher pregnancy rates when compared to primiparous cows. The introduction of GnRH and eCG in random conditions of the estrous cycle and in cyclical females with good body score can be dispensed with, reducing the cost of the final protocol.